A novel magnetorheological valve with meandering flow path structure - Imaduddin, Fitrian (2015)
The development of a new Magnetorheological (MR) valve with meandering flow path as a new approach to improve the MR valve performance is presented in this research. The meandering flow path was formed by the arrangement of multiple annular and radial channel so that the total effective area in an MR valve can be increased without compromising the size and power requirement of the valve. The main objective of this research is to explore the achievable pressure drop of the MR valve with meandering flow path. This research was started with the concept development where the meandering flow path structure is analytically modeled and numerically simulated to predict and analyze the effect of variables involved. The prediction results showed that the meandering flow path structure is able to increase the achievable pressure drop of an MR valve significantly. The gap size analysis showed that the size of annular gaps mainly contributed to determine the viscous pressure drop component. Meanwhile, the field-dependent pressure drops were mainly determined by the size of radial gaps. The prediction results of the concept was also assessed and confirmed by the experimental work using a dynamic test machine. Based on the experimental data, two hysteresis models, namely the polynomial model and the modified LuGre model, were developed to model the hysteresis behavior. The assessment results of the hysteresis models indicated that both model were able to replicate the hysteresis behavior. However, the modified LuGre model, though 9.5% less accurate than the polynomial model, was showing better consistency in a wider range of input values. In general, the new concept contributes in the development of a new type of MR valve that could achieve pressure drop nearly three times than the annular, radial and annular-radial type MR valve.